Nutmeg oil production process analysis using Business Process Improvement-a case study. Issue 1 (February 2021) - Darma, R; Sastra, H Y; Arhami,; Erwan, F
Abstract: This study delivers the analysis of business process of the nutmeg oil production process in a small and medium enterprise (SME) in South Aceh using Business Process Improvement (BPI). This study analyses the pre-refining, refining and post refining activities of the nutmeg oil production process based on economics, labour, and technology aspects. This study carries out 3 phases of BPI which are organizing for improvement, understanding the process, and streamlining. This study reveals activity efficiency from 31 (on the as-is model) to 26 (on the to-be-model). The activities are further analysed using Devil's Quadrangle, particularly for cost and time dimensions. As a result of the new technology implementation being proposed, the fixed cost has increased by 48.33%, the variable cost has decreased by 47.64% and time has improved by 33.33%. Moreover, this study provides a recommendation to implement the to-be-model of the business process as an SOP for the nutmeg oil production process in South Aceh SMEs.